Balanço hídrico na sub-bacia hidrográfica do Boi Branco – SP para gestão sustentável da agricultura irrigada - Sales, Mariana Alexandre de Lima [UNESP] (2014)
The water resources are fundamental to the development of several economic activities. Concerning the agriculture production, the water can represent close to 90% of the physical constitution of the plant. The low water supply during the growing stage of vegetables can make the agricultural production not viable and can even seriously affect the balance of the ecosystem. One way to calculate the amount of water in a determined system is by means of the water balance, that is an important tool for the assessment process of the water cycle in a specific region or specific crop, as it represents the sum of water quantity that gets in and out of a given system, in a given time range, whose result indicates - during the assessed period - if there is a shortage or excess of water for the crop. Its importance is essential for the studies on the water regime, agriculture planning, zoning, climate studies, among other uses. The main goal of this work was to establish the water balance in the watershed Boi Branco-SP, so that it can be used as a tool for the hydro-agricultural and environmental planning of the region. The water climate balance in a monthly scale was determined with the aim to recognize the water availability in the region. It was also determined the water balance of tillage for the irrigation control in the different crops of the watershed, aiming to verify the most critical periods of low water supply in the soil, making it possible a better water management. The required data for water balance calculation are the precipitation, evapotranspiration, given by the installed crop and water holding capacity in the soil (WHC). For the water climate balance, it was used data of the historical series of the region, available in pluviometric stations located in the studied area. It was ...